2021
DOI: 10.1108/ijsms-01-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Sport rebranding: the effect of different degrees of sport logo redesign on brand attitude and purchase intention

Abstract: PurposeDespite its growth, there has been a lack of investigation on how sport rebranding influences fans and their behaviors. This study sought to examine how a critical aspect of rebranding – logo redesign – influences fans' attitudes toward a sport brand and intent to purchase merchandise bearing the rebranded logo. More specifically, we aim to investigate the influence of varying degrees of logo change and fan identification in relation to brand attitude and purchase intention.Design/methodology/approachAn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Some studies have explored the impact of different types of logos and brand visibility on consumers' negative attitudes. In a study by Williams and Son (2022) on the redesign of sports logos and its effects on brand attitudes and purchase motivation, it was found that both highidentified and low-identified customers had significantly negative attitudes toward logo color changes and revolutionary alterations. Additionally, high-identified fans showed larger reactions to logo changes, challenging their recognition habits and causing discomfort, while low-identified fans' reactions were not significant.…”
Section: Logo and Brand Attitudes Brand Evaluationmentioning
confidence: 99%
“…Some studies have explored the impact of different types of logos and brand visibility on consumers' negative attitudes. In a study by Williams and Son (2022) on the redesign of sports logos and its effects on brand attitudes and purchase motivation, it was found that both highidentified and low-identified customers had significantly negative attitudes toward logo color changes and revolutionary alterations. Additionally, high-identified fans showed larger reactions to logo changes, challenging their recognition habits and causing discomfort, while low-identified fans' reactions were not significant.…”
Section: Logo and Brand Attitudes Brand Evaluationmentioning
confidence: 99%
“…), there have been studies that have evaluated logos in the context of sport. Many of these studies examine professional sport team logos, specifically analyzing the utilization of rebranding techniques (Williams and Son, 2022). Pedersen and Williams (2022), using a framework of analysis provided by sport team and business logo research, performed a content analysis to assess the current trends of logo usage by professional athletes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The attractiveness of a brand logo influences customers' commitment to the brand (Park et al, 2013) and can shape brand reputation (Park et al, 2013). Brand logos can impact the brand attitude and purchase intention (Williams & Son, 2022) and perceptions of the brand's products (Bettels & Wiedmann, 2019), positively affect brand personality, and shape the emotional response of customers toward the brand (Kaur & Kaur, 2019). When shopping, a brand logo can trigger positive associations with the brand, helping consumers choose trusted products (Henderson & Cote, 1998; Park et al, 2013; Walsh et al, 2010).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%